Expression screening using a Medaka cDNA library identifies evolutionarily conserved regulators of the p53/Mdm2 pathway - Zhang, Ping; Wittbrodt, Joachim (BMC biotechnology, 2015)
The p53 tumor suppressor protein is mainly regulated by alterations in the half-life of the protein, resulting in significant differences in p53 protein levels in cells. The major regulator of this process is Mdm2, which ubiquitinates p53 and targets it for proteasomal degradation. This process can be enhanced or reduced by proteins that associate with p53 or Mdm2 and several proteins have been identified with such an activity. Furthermore, additional ubiquitin ligases for p53 have been identified in recent years. Nevertheless, our understanding of how p53 abundance and Mdm2 activity are regulated remains incomplete. Here we describe a cell culture based overexpression screen to identify evolutionarily conserved regulators of the p53/Mdm2 circuit. The results from this large-scale screening method will contribute to a better understanding of the regulation of these important proteins. Expression screening was based on co-transfection of H1299 cells with pools of cDNA’s from a Medaka library together with p53, Mdm2 and, as internal control, Ror2. After cell lysis, SDS-PAGE/WB analysis was used to detect alterations in these proteins. More than one hundred hits that altered the abundance of either p53, Mdm2, or both were identified in the primary screen. Subscreening of the library pools that were identified in the primary screen identified several potential novel regulators of p53 and/or Mdm2. We also tested whether the human orthologues of the Medaka genes regulate p53 and/or Mdm2 abundance. All human orthologues regulated p53 and/or Mdm2 abundance in the same manner as the proteins from Medaka, which underscores the suitability of this screening methodology for the identification of new modifiers of p53 and Mdm2. Despite enormous efforts in the last two decades, many unknown regulators for p53 and Mdm2 abundance are predicted to exist. This cross-species approach to identify evolutionarily conserved regulators demonstrates that our Medaka unigene cDNA library represents a powerful tool to screen for these novel regulators of the p53/Mdm2 pathway.
Gesehen am 31.01.2017